2018
DOI: 10.1002/jum.14862
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of 2 Liver 2‐Dimensional Shear Wave Elastographic Techniques in the Fasting and Postprandial States

Abstract: Objectives-The purpose of this study was to compare the reliability and agreement of 2 methods of 2-dimensional (2D) shear wave elastography (SWE) on liver stiffness in healthy volunteers. We also assessed effects of the prandial state and operator experience on measurements.Methods-Two operators, 1 experienced and 1 novice, independently examined 20 healthy volunteers with 2D SWE on 2 ultrasound machines (Aixplorer [SuperSonic Imagine, Aix-en-Provence, France] and Aplio 500 [Canon Medical Systems Corporation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The absolute SWE values in our cohort (mean 4.37 ± 0.60 kPa) are comparable to already published data in children ( 16 , 44 47 ) but lower than the mean values in other studies ( 48 50 ), possibly due to the usage of different ultrasound devices. Fasting duration did not significantly influence SWE in our study, as suggested by Simkin et al ( 51 ). However, there are conflicting data from adult studies ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 85%
“…The absolute SWE values in our cohort (mean 4.37 ± 0.60 kPa) are comparable to already published data in children ( 16 , 44 47 ) but lower than the mean values in other studies ( 48 50 ), possibly due to the usage of different ultrasound devices. Fasting duration did not significantly influence SWE in our study, as suggested by Simkin et al ( 51 ). However, there are conflicting data from adult studies ( 52 , 53 ).…”
Section: Discussionsupporting
confidence: 85%
“…No information was obtained about reproducibility or interobserver agreement on SWE values. Several earlier studies, however, have shown high reproducibility and interobserver agreement [33][34][35] of SWE measurements, if some consistent technical requirements (same type of elastography, eg, MRE or SWE, static or dynamic, ideally use of the same ultrasound device) are fulfilled. 24 Absolute quantitative SWE values might differ intraindividually and interindividually, if different techniques are used.…”
Section: Limitationsmentioning
confidence: 96%
“…HVPG and liver stiffness measurement with both VCTE and 2D-SWE.GE were performed on the same day after at least 6 hours (overnight) fasting [12][13][14].…”
Section: Patients and Study Protocolmentioning
confidence: 99%